CARBOHYDRATE CONSUMPTION LUNCH, CENTRAL OBESITY AND BLOOD GLUCOSE LEVELS IN LABOUR AT INAYA HOTEL PUTRI BALI, BADUNG - Kadek Wulan Dwi Kusuma; Pande Putu Sri Sugiani; Lely Cintari (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2022)
Carbohydrate consumption in the workforce will indirectly affect the nutritional status and blood glucose levels of the workforce. If someone is over consuming carbohydrates accompanied by a lack of physical activity carried out will cause central obesity. The purpose of the study was to obtain carbohydrate lunch consumption, nutritional status and blood glucose levels in the workforce at the Inaya Putri Bali Hotel, Badung. The population of this research is the back office workforce with a large sample size of 48 samples. Data collected in May 2019 using the cross sectional method by performing a recall 1 times 24 hours for workers. Data taken consists of 2 data, namely primary data and secondary data, analyzed using cross tables accompanied by narration. the results of study carbohydrate consumption in the sample of the majority of the samples were in the less category. While the nutritional status of the sample is obtained, some samples have more nutritional status based on waist circumference. Blood glucose levels in the sample showed that most of the samples had blood glucose levels in the uncertain DM category with a range of 90 - 199 mg / dl. Therefore it is expected to set the standard of food portions on labor to prevent central obesity.